Scenario Planning of Hybrid Working Model Effectivity (Work From Home & Work From Office) at PT. XYZ - Novalinda Simanjuntak; M. Syamsul Maarif; Harri Kuswanda (Business Review and Case Studies, 2023)
The research objective is to analyze the effects of leadership and work-life balance on the performance of PT XYZ employees, to analyze the effects of work-life balance and employee engagement on the performance of PT XYZ employees, and to formulate the scenario planning of the effectivity of hybrid working model that can be suggested to PT XYZ. The sample of this study is employees of PT XYZ who have been working for at least 6 months in the hybrid working model, particularly at non production divisions. The evaluated variables in this study are work-life balance, employee engagement, leadership dan performance. The survey data is collected from 104 respondents who filled out the online questionnaire (Google Form) and from 8 experts via discussion and interview sessions. This study used a descriptive analysis, PLS-SEM and TAIDA (Tracking, Analyzing, Imaging, Deciding, and Acting) methods. The results showed that work-life balance had positive and significant effects on employee engagement and leadership but it does not have significant effect on performance, employee engagement had positive and significant effects on leadership and performance, as well as leadership had positive and significant effects on performance. Regarding the managerial impact, the hybrid work model affected the cost, people and technology that moreover it can be an added value for the company. Keywords: hybrid work model, work from home, work from office, scenario planning, TAIDA